Action Sports and the Olympic Games: Past, Present, Future - Belinda wheaton; Holly Thorpe (Routledge, 2022)
Based on a decade of research by two leading action sports scholars, this book maps the relationship between action sports and the Olympic Movement, from the inclusion of the first action sports to those featuring for the first time in the Tokyo Olympic Games and beyond. In an effort to remain relevant to younger audiences, four new action sports, surfing, skateboarding, sport climbing, and BMX freestyle were included in the Tokyo Olympic program. Drawing upon interviews with Olympic insiders, as well as leaders, athletes, and participants in these action sports communities, the book details the impacts on the action sports industry and cultures, and offers national comparisons to show the uneven effects resulting from Olympic inclusion. It reveals the intricate workings of power and politics in contemporary sports organisations, and maps key trends in this changing sporting landscape. Action Sports and the Olympic Games is a fascinating read for anybody studying the Olympics, the sociology of sport, action sports, or sport policy.
Keywords: 790; Olympic Inclusion; Sport Climbing; Belinda Wheaton; Action Sport Cultures; Holly Thorpe; Action Sport Industries; Olympic Games; Action Sports; Agenda 2020; Action Sport Participants; BMX Freestyle; lifestyle sports; Surfing Industry; windsurfing; World Skate; mountain biking; Young Men; surfing; Action Sport Athletes; snowboarding; International Olympic Committee; skateboarding; IOC; Youth Olympic Games; Surfing Culture; Tokyo 2020; ISA; kitesurfing; Olympic Programme; gender and sport